The Role of K+, Ca2+ channels and Endothelial Hyperpolarizing Factors in Vasorelaxation Induced by Tribulus terrestris - Bashir , Thamer M.; Al-Habib, Omar A.M. (Technium BioChemMed, 2021)
The present study focused on the relaxant effect of themethanolic extract (ME) of Tribulus terristris on rats’ thoracic aortae and included the study of underlying vasorelaxation mechanisms. The methanolic extract produced concentration-dependent relaxation in rats’ aorta. The methanolic extract produced concentration-dependent relaxation in the aortic rings. The use of different K+ channel blockers (BaCl2, 4-AP, GLIB, and TEA) indicated that Kv, KATP, KIR, and KCa and L-type Ca channels played no role in the methanolic extractinduced relaxation. However, with respect to endothelium-derived hyperpolarizing factors, PGI2 and sGC produced a mild inhibition in the relaxation response to ME while NO produced no effect at all. Based on the novel results of the current study, it can be concluded that T. terrestris methanolic extract (ME) mediated relaxation in isolated rat aortic tissues in a concentration-dependent manner. Moreover, we discovered that ME-mediated relaxation is endothelium-dependent and that potassium and calcium ion channels play no role in this relaxation with a limited role of PGI2 and sGC.